A diketopyrrolopyrrole-based fluorescent porous organic polymer as fluoride sensing monolithic device. Issue 15 (21st March 2018) - Bi, Shiming; Li, Yankai; Zhang, Shaoze; Hu, Jun; Wang, Limin; Liu, Honglai
Abstract : Diketopyrrolopyrrole-based fluorescent porous organic polymer was successfully immobilized on a macroporous sponge to obtain a fluoride sensing monolithic device. Abstract : Diketopyrrolopyrrole-based moiety was polymerized with tetrakis(4-ethynylphenyl)methane to afford a porous organic polymer with good porosity and accessible active sites. This polymer inherited the fluorescent nature of parent monomer and underwent colorimetric and fluorescence change upon the exposure to fluoride anions. Remarkably, a superior selectivity towards fluoride anions was observed with the limit of detection of 18 ppb. Moreover, the polymer could be recycled several times. Finally, the porous organic polymer was successfully immobilized on a macroporous sponge to obtain a fluorescence sensing device, which was efficient in detection and was easier to handle when compared with the device obtained using polymer powder.